Emerging Trends in Snake Venom-Loaded Nanobiosystems for Advanced Medical Applications: A Comprehensive Overview - Álisson E. F. Alves; Anne B. C. Barros; Lindomara C. F. Silva; Lucas M. M. Carvalho; Graziela M. A. Pereira; Ana F. C. Uchôa; José M. Barbosa-Filho; Marcelo S. Silva; Karla P. O. Luna; Karla S. R. Soares; Francisco H. Xavier-Júnior (Pharmaceutics)
Advances in medical nanobiotechnology have notably enhanced the application of snake venom toxins, facilitating the development of new therapies with animal-derived toxins. The vast diversity of snake species and their venom complexities underline the need for ongoing research. This review is dedicated to exploring the integration of snake venom with nanoparticles to enable their use in human therapies aiming to develop treatments. The complex mixture of snake venom not only inflicts significant pathological effects but also offers valuable insights for the creation of innovative therapies, particularly in the realm of nanobiotechnology. Nanoscale encapsulation not only mitigates the inherent toxicity of snake venom but also amplifies their antitumoral, antimicrobial, and immunomodulatory properties. The synergy between venom-derived macromolecules and nanotechnology offers a novel pathway for augmenting the efficacy and safety of conventional antivenom therapies, extending their applicability beyond treating bites to potentially addressing a myriad of health issues. In conclusion, nanotechnology presents a compelling therapeutic frontier that promises to improve current treatment modalities and ameliorate the adverse effects associated with venomous snakebites.